REKONSTRUKSI INKLUSI SOSIAL DAN KEADILAN GENDER PADA KELUARGA MUDA RENTAN EKONOMI: TINJAUAN PPKN TERHADAP KRISIS PERAN ORANG TUA DALAM PEMBENTUKAN KARAKTER ANAK - Chandra Fhutu Neva; Nurur Risky Aulia; Andry Anshari; Raysyah Putri Sitanggang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The phenomenon of the parental role crisis in character building is a crucial issue for young families facing economic vulnerability. This research is driven by structural challenges within the child protection system that have not effectively reached the grassroots level. The study aims to formulate a family inclusion model based on "Prososial Networks" to strengthen children's character within the framework of Citizenship Education (PPKn). This research uses a qualitative approach, identifying that economic vulnerability and gender norms significantly impact parenting dynamics. The results indicate that an intervention framework integrating global issues (such as child penalty) and local citizenship is essential for sustainable social inclusion. The research results are manifested in a validated policy brief and character-strengthening module relevant to community-level child protection in Labuhanbatu Selatan.